1990
DOI: 10.2136/sssaj1990.03615995005400030035x
|View full text |Cite
|
Sign up to set email alerts
|

Organic Amendment Effects on Physical and Chemical Properties of a Sandy Soil

Abstract: Effects of repeated applications of sewage‐sludge compost on soil properties have not been sufficiently evaluated with field trials. Field studies were established on an Evesboro loamy sand soil (mesic, coated Typic Quartzipsamment, 97% sand) to compare the effects of sewage‐sludge compost, beef manure, and fertilizer amendments on soil properties. The study site had been fallow for 26 yr and should have provided a positive response to the added organic matter. Compost application rates were based on the assum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
105
3
14

Year Published

1996
1996
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(134 citation statements)
references
References 0 publications
12
105
3
14
Order By: Relevance
“…A significant decrease in bulk density with an associated increase in total porosity of soil under sesbania is probably related to greater amount of organic matter deposition and loosening of soil by root action (Haynes, 2000;Lampurlanes and CanteroMartinez, 2003). Bulk density is inversely related to total porosity, which provides a measure of the porous space left in the soil for air and water movement (Min et al, 2003;Tester, 1990). Lower bulk density implies greater pore space and improved aeration, developing a suitable environment for biological activity (Islam and Weil, 2000-b;Min, et al, 2003;Werner, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant decrease in bulk density with an associated increase in total porosity of soil under sesbania is probably related to greater amount of organic matter deposition and loosening of soil by root action (Haynes, 2000;Lampurlanes and CanteroMartinez, 2003). Bulk density is inversely related to total porosity, which provides a measure of the porous space left in the soil for air and water movement (Min et al, 2003;Tester, 1990). Lower bulk density implies greater pore space and improved aeration, developing a suitable environment for biological activity (Islam and Weil, 2000-b;Min, et al, 2003;Werner, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Green manuring crops, like sesbania specifically influence soil structural properties by enmeshing soil primary particles and microaggregates into macroaggregation through direct physical action of roots, and production of cementing agents from enhanced microbial activities. These aggregation processes and properties may reduce soil bulk density and increase porosity with greater water retention and transmission capacities (Goldhamer, et al, 1994;Hargrove, et al, 1989;Islam and Weil, 2000-b;Min, et al, 2003;Tester, 1990;Werner, 1997). Likewise Chikowo, et al (2004) reported that incorporation of woody legumes into the soil reduces bulk density and increases soil granulation and porosity.…”
Section: Discussionmentioning
confidence: 99%
“…Organic compost increases soil carbon sequestration and reduces GHGs emission (Forte et al 2017). It enriches SOM, soil fertility, soil microbial diversity, soil moisture, cation exchange capacity, soil aeration and reduces soil erosion and crop pests and diseases (Tester 1990;Diaz-Zorita et al 1999;Peacock et al 2001;Mäder et al 2002;Magdoff and Weil 2004;Sun et al 2004;Fließbach et al 2007;Ge et al 2008;Zhang et al 2012;Liu et al 2013). It is widely recognized that animal manure and crop straw enhance the SOM and crop yield (Yang et al 2004).…”
Section: Traditional Organic Compostingmentioning
confidence: 99%
“…Moreover, it can allow the management of large amounts of wastes generated by urban settlements and agro-industrial processes, after their transformation by composting process, and in addition, it can improve plant resistance and plant protection by stimulating root development by recycling plant nutritive elements (De Bertoldi, 2008). Many organic material wastes represent an important resource of nitrogen, phosphorous, calcium and other elements as zinc, copper and magnesium essential to plant growth (Tester, 1990). There are sufficient data to indicate that organic materials reduce disease incidence caused by a wide range of plant pests including bacteria, soil-borne pathogens and phytoparasitic nematodes species (D'Addabbo et al, 1997;Abawi & Widmer, 2000;Bailey & Lazarovits, 2003;Renčo et al 2007Renčo et al , 2009Renčo et al , 2010Hu & Qi, 2010).…”
Section: Introductionmentioning
confidence: 99%